Penanganan Gangguan Belajar Anak Disleksia Melalui Spelling Method - Nurita Sari; Raden Rachmy Diana; Nadia Aliyatuz Zulfa (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
Everyone has different abilities and levels of intelligence, including children with learning difficulties such as dyslexia. Dyslexia is a neurological brain disorder that affects reading and writing skills, rather than being the result of poor learning. It involves challenges in information processing in the brain, so dyslexic children often have difficulty reading words quickly and accurately. This research aims to analyze the treatment of learning disorders of dyslexic children through the spelling method. The methodology used in this research involves a qualitative approach using case studies. The data collection techniques used were observation, interview and documentation. The observation and interview techniques used question guidelines that had been prepared, while documentation was carried out with data analysis techniques which included data reduction, data presentation, and conclusion drawing. The results of this study show that the spelling method is an effective teaching technique for children with dyslexia. This method involves phonetic understanding, phonological awareness, as well as a consistent and collaborative multi-sensory approach between schools and parents. The studied child showed significant improvement in reading ability after the application of this method, through repeated practice and periodic evaluation that ensures effectiveness and supports the achievement of the child's academic potential.